2020
DOI: 10.1212/cpj.0000000000000776
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and chikungunya infection in neurologic disorders from endemic areas in Brazil

Abstract: Objective To detect the frequency of dengue virus (DENV), Chikungunya virus (CHIKV), and Zika virus (ZIKV) in adult patients with suspected viral infection of the CNS or postinfectious syndromes living in the state of Rio de Janeiro, Brazil. Methods DENV, CHIKV, and ZIKV RNA by reverse transcription PCR (RT-PCR) and specific IgM antibodies were investigated in 47 CSF and serum samples of 36 adult patients suspected with viral infection or postinfectious neurologic diseases. In addition, intrathecal synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In a previous study, our group found 31% of cases of neuroinvasive arboviruses (DENV/CHIKV) by RT-PCR and specific IgM in the CSF and/or serum in patients with suspected infectious or post-infectious neurological disorders (encephalitis, GBS, optic neuritis, neuromyelitis optic spectrum disorder, polyneuropathy, and myelitis). This analysis showed the importance of routine CSF investigations in endemic areas 36 .…”
Section: Discussionmentioning
confidence: 73%
“…In a previous study, our group found 31% of cases of neuroinvasive arboviruses (DENV/CHIKV) by RT-PCR and specific IgM in the CSF and/or serum in patients with suspected infectious or post-infectious neurological disorders (encephalitis, GBS, optic neuritis, neuromyelitis optic spectrum disorder, polyneuropathy, and myelitis). This analysis showed the importance of routine CSF investigations in endemic areas 36 .…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, we found normal leukocyte counts instead of the classical leukopenia of dengue with warning signs or severe dengue, which pose a difficulty to early diagnosis, although there was thrombocytopenia only at day six of hospitalization with no changes in ALT and AST transaminases as reported previously. Recently, 11/36 patients from a Brazilian endemic area were diagnosed with neurologic manifestations and confirmed for arbovirus infection using CSF or sera [ 32 ] (5 DENV and 6 CHIKV), posing an additional warning about involvement of these viruses in severe disease presentation in Latin-American countries where there is cocirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue is not considered a neurotropic virus. However, neurotropism and neuro-invasion have been reported previously [ 55 , 69 ], and encephalitis and encephalopathy are the most common neurological presentations of DENV infections [ 70 , 71 , 72 ]. It is estimated that 0.5–21% of DENV-infected patients develop neurologic manifestations, with DENV-2 and DENV-3 most frequently associated with cases of myelitis, meningitis, and encephalitis [ 70 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%